Konsumsi Jagung Manis Sebagai Sumber Pangan Alternatif Syarat Gizi Pencegah Stunting Pada Balita Di Desa Kampung Jawa Blangkejeren Gayo Lues - Mario Pani; Rahayu Eka Sari; Ali Makmur; Anuar Ramut; Joharsah Joharsah; Habibul Akram; Fitri Wahyuni; Muhammad Husaini Assauwab (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
One of the consequences of poor nutritional management in toddlers is stunting. One nutritious alternative food to prevent stunting at a relatively cheaper price is sweet corn. Sweet corn is increasingly popular and widely consumed because it has a sweeter taste than regular corn (Kartika, 2019). Siswono (2004 in Surtinah, 2013) reported that the sugar content of the master sweet variety is 16 – 18%, close to the sugar content of cane, namely 19%. Sweet corn contains 96 cal Energy, 3.5 g Protein, 1.0 g Fat, 22.8 g Carbohydrates, 3.0 mg Calcium, 111 mg Phosphorus, 0.7 mg Iron, Vitamin A 400 SI, Vitamin B 0, 15 mg, Vitamin C 12.0 mg, and water 72.7 g Iskandar, 2006). This service activity was carried out at the Kampung Jawa Village Hall, Blangkejeren District, Gayo Lues Regency. The parties involved in this activity were lecturers from the Agrotechnology and Forestry study program, PSDKU Gayo Lues, Faculty of Agriculture, Syiah Kuala University as resource persons, as well as the Agrotechnology and Animal Husbandry study program, Faculty of Agriculture, Gunung Leuser University, Aceh Kutacane, village midwives as partners, village heads as facilitators and the village community. Javanese Village as a participant. Survey of activity locations, socialization of service activities, implementation of service activities, evaluation of service activities. The conclusions from this activity are: 1. Regarding the causes, characteristics, dangers and prevention of stunting by related parties, this is one of the first steps in efforts to improve the nutrition of pregnant women and toddlers in the Kampung Jawa Village community. 2. Sweet corn is an alternative food source that can be consumed by pregnant women and toddlers to prevent stunting. 3. This activity attracts the attention of mothers participating in socialization and Posyandu in Kampung Jawa Village and can increase their knowledge about preventing and handling stunting.